Endoscopic Endonasal Approach of Congenital Meningoencephalocele Surgery: First Reported Case in Lithuania - Svajūnas Balseris; Giedrius Strazdas; Saulius Ročka; Tomas Jakštas (Case Reports in Otolaryngology)
Meningoencephalocele is a rare condition that usually occurs in children and is treated by neurosurgeons with occasional help from ENT doctors. The symptoms of meningoencephalocele might not develop until adulthood, but usually they are apparent immediately after birth. The case of small anterior basal transethmoidal meningoencephalocele in a 24-year-old patient who had headaches and runny nose since childhood is presented. Endonasal endoscopic approach for meningoencephalocele removal and skull base defect reconstruction was used. It was concluded that endoscopic endonasal approach is less invasive and provides an acceptable operative outcome with short recovery time and less postoperative complications in comparison with other external microsurgical approaches.